Comprehensive Characterization of Microbial Community in the Female Genital Tract of Reproductive-Aged Women in China - Sun, Ningxia; Ding, Haixia; Yu, Hongjing; Ji, Yixuan; Xifang, Xiuyue; Pang, Wenjuan; Wang, Xiang; Zhang, Qing; Li, Wen (Frontiers in Cellular and Infection Microbiology, 2021)
Microbiota in human body play critical roles in many physiological and pathological processes. However, the diversity and interior dynamic of microbiota within female genital tract (FGT) has not been fully unveiled. In this study, we characterized the microbiome variations in reproductive-aged Chinese women, and revealed that microbiota like Lactobacillus dominated in the vagina and cervix. Overall, microbiota in uterine cavity were more diverse than those in vagina and cervix. A symbiotic relationship between Lactobacillus iners and Lactobacillus crispatu was observed in both vagina and cervix. Moreover, we for the first time stratified the Chinese reproductive-aged women into subgroups based on the microbiome profiles. Furthermore, we identified the bacteria with changed abundance in the uterine cavity of infertile patients, such as Acinetobacter junii and Propionibacterium acnes. Functionally, metabolism-related pathway, neurotrophin signaling pathway and adipocytokine signaling pathway were predominantly dysregulated in the uterine cavity of infertile patients. In conclusion, we characterized a comprehensive microbial landscape in FGT, as well as their biological functions involved in female infertility of Chinese population.